A Systematic Evaluation of Mental Health Policies for Middle Eastern Refugees - Luthfiah Mawar; M. Agung Rahmadi; Helsa Nasution; Nurzahara Sihombing (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
This meta-review study presents a comprehensive evaluation of the effectiveness of mental health policies targeting refugees from the Middle East based on a systematic analysis of 87 policies issued across 12 refugee-hosting countries during the period from 2015 to 2023. Employing the PRISMA approach and thematic analysis, this research found that only 34.5% of all reviewed policies met the World Health Organization's minimum standards regarding mental health services for refugees. In comparison, the effective implementation rate of those policies meeting the standards reached only 28.7% (CI 95%, p<0.001). Findings from the logistic regression analysis revealed a significant correlation between the scale of mental health budget allocations and recovery rates from PTSD among refugee populations, where every 10% increase in budget allocation corresponded to a 15.3% reduction in PTSD prevalence (r=0.78, p<0.001). Furthermore, the meta-analysis results from this study demonstrated that community-based policies were 2.4 times more effective (OR=2.4, CI 95%: 1.8–3.1) than those employing institutional approaches. Hence, diverging from the conclusions posited by Turrini et al. (2019) and Sijbrandij (2017), which emphasized clinical interventions, this study has instead affirmed that integrating cultural-spiritual approaches with conventional therapy can enhance treatment success by 47.2%. Additionally, these findings expand the conceptual framework previously proposed by Watters (2001) on holistic approaches by identifying five key elements that form the foundation of effective mental health policies: universal access, cultural sensitivity, community empowerment, service integration, and program sustainability.